The urban soundscape: analysing the spatiotemporal distribution of acoustic events and its influence on the racial/ethnic composition of New York City neighbourhoods - Faruqi, Shuraifa Asmah Shad Saleem (Universiti Pendidikan Sultan Idris, 2018)
The urban soundscape: analysing the spatiotemporal distribution of acoustic events and its influence on the racial/ethnic composition of New York City neighbourhoods by Faruqi, Shuraifa Asmah Shad Saleem